214 Glycated LDL (glyc-LDL) Promotes Osteogenic Differentiation of Vascular Smooth Muscle Cells. (6th June 2015) - Weston, Ria; Wilkinson, Fiona; Liu, Yifen; Schofield, Jonathan; Siahmansur, Tarza; Soran, Handrean; Alexander, Yvonne
Abstract : Introduction: It is well established that glyc-LDL is elevated in the serum of diabetic patients compared to healthy subjects, and that vascular calcification is common in diabetes. Furthermore, recent studies suggest that advanced glycation end products may play a pathogenic role in vascular calcification. We hypothesise that glyc-LDL promotes the osteogenic differentiation of vascular smooth muscle cells in vitro . Methods: LDL was isolated from human serum by sequential density gradient ultracentrifugation and incubated at 37°C with a range of glucose concentrations at different time points to determine the optimum glycation conditions. The glyc-LDL was measured using an in-house ELISA method. Bovine Aortic Smooth Muscle Cells (BAoSMCs) were incubated with native or glycated LDL in the presence of osteogenic media and mineral deposition was determined using alizarin red staining and alkaline phosphatase (ALP) activity, which is an early marker of osteogenesis. Results: The optimum conditions for LDL glycation was determined as 80mM glucose for 7 days, so these conditions were used for the production of glycated LDL throughout the study. BAoSMCs incubated in osteogenic media exhibited mineralisation after 7 days as determined by alizarin red staining. This calcification was significantly enhanced by treatment with glyc-LDL, but not by native LDL. Furthermore, we found that ALP activity was significantly elevated as early as day 4 in glyc-LDL treated cells, compared to those incubated in native LDL. The glyc-LDL-induced mineralisation was not attenuated in the presence of osteoprotegrin (OPG) nor in the presence of two novel small RAGE antagonist peptides, which were designed to prevent RAGE binding with several of its most important ligands, including HMGB-1, S100P and S1004A. Conclusion: We have shown that human-derived glyc-LDL accelerates vascular calcification in vitro . This process does not appear to be attenuated by the addition of OPG, suggesting AGE-induced accelerated calcification occurs through a pathway independent of the RANKL/OPG signalling activity. Further studies with a range of RAGE inhibitors should allow the identification of the molecular pathways implicated in glyc-LDL induced calcification to enable the development of therapeutic peptides effective in blocking of RAGE-ligand interaction, which is prevalent in many pathologies.